Berardinelli-Seip congenital lipodystrophy in two siblings - T Rao; Kavya Chennamsetty (Wolters Kluwer Medknow Publications, 2014)
Berardinelli-Seip congenital lipodystrophy (BSCL) is a very rare autosomal recessive disorder characterized by various dermatological and systemic manifestations such as lipoatrophy, hypertriglyceridemia, hepatomegaly, acanthosis nigricans, and acromegaloid features. BSCL type 2 is more common and severe, with onset in the neonatal period or in early infancy. The locus for BSCL2 has been identified on chromosome 11q13. Early recognition and differentiation from other congenital generalized lipodystrophies help in the initiation of appropriate preventive and therapeutic measures such as lifestyle modification and pharmacotherapy that helps postpone the onset of metabolic syndrome. We report BSCL type 2 in two siblings with several cutaneous manifestations like acanthosis nigricans, hypertrichosis, prominent subcutaneous veins, and increased lanugo hair.